Increasing productivity of valuable agarwood in Senggreng Village, Malang Regency - Eka Larasati Amalia; Mustika Mentari; Vivin Ayu Lestari; Farida Ulfa; Vivi Nur Wijayaningrum; Lia Agustina (University of Merdeka Malang, 2023)
Wisma Gaharu as one of the plantations assisted by the Malang Regency Perhutani Service conducts an agarwood nursery with the species Gyrinops Versteegii. However, the agarwood plants cultivated at Wisma Gaharu are attacked by caterpillars annually, causing damage to the agarwood leaves. Accordingly, the growth of agarwood plants is hampered, and further dry out and die. This causes the owner of Wisma Gaharu to suffer huge losses, especially if the pest attacks the plant which is ready for the inoculation process in the dry season. To overcome this, agarwood farmers must pay high attention and vigilance to fight agarwood caterpillar attacks that occur throughout the year since it is considered the most dangerous pest for plants. The unavailability of production support equipment is one of the problems faced by Wisma Gaharu; there is also a need for work safety training (K3) regarding proper supporting equipment use considering the risks faced by workers in the agriculture sector. The above problems underline the main reasons for supporting equipment procurement and administering work safety training.